Identification and Characterization of Marek’s Disease Virus Serotype 1 Using Molecular Approaches - Risza Hartawan; NLPI Dharmayanti (Indonesian Center for Animal Research and Development, 2015)
Marek’s disease is an important disease in the commercial poultry farm and causes significant economical loss. The disease is characterized by syndrome of paralysis and neoplastic formation in various organs and tissues in the host. The etiological agent is Marek’s disease virus serotype 1 (MDV-1). Eventhough the outbreaks in the field are well controlled by vaccination, several cases in the vaccinated flocks indicating virus evolution into more pathogenic strains. Therefore, monitoring of the disease circumstance in the field is indispensable for guiding better policies in disease controlling program. This paper describes several molecular methods that have been developed for identification and characterization of MDV-1. The identification and characterization of newly found virus strain in the field can be done by in vivo challenge test which is a conventional method especially to determine pathogenecity. However, this method requires several stages with time consuming procedures. The development of alternative methods for identification and characterization of MDV-1 viruses has been conducted mainly using molecular biology approach. Several molecular methods give satisfying result and have been implemented in both laboratory and field condition. Key words: Marek’s disease virus serotype 1, identification, characterization, molecular